Sensory stimuli that support a child's recovery in the therapeutic environment (Journal of Namibian Studies : History Politics Culture, 2023)
Caring for and treating a child's health is an important need to achieve optimal health? It is a concept that reaches beyond mere recovery from illness. It's achieved by balancing the different aspects of the child, including physical, psychological, mental, and spiritual aspects.A sick child needs therapeutic environments that provide medical care in a way that accelerates the recovery process. The therapeutic environment for the child prefers to be positive and conscious with its incentives that enhance the child's ability to receive treatment, reduce their fear and anxiety and distract them from the disease, which provokes positive feelings and helps them to recover quickly.Here comes the great role that pediatric hospitals play through their design style, which addresses dimensions related to the concepts of therapeutic indoor spaces and their financial and psychological impact on the child and thus their impact on the healing process